Efeito do tabagismo no prognóstico da tuberculose pulmonar em pacientes internados no HUJBB - LIMA, Manoel Macirio Oliveira (2023)
Tuberculosis (TB) is a multisystem infectious disease, which mainly affects the lungs, presents a chronic evolution, its main etiological agent, Mycobacterium tuberculosis. In 2021, Pará had a higher incidence rate than the national one, reaching a value of 42. Active tobacco consumption is related to an increased risk of tuberculosis of about 2.5 times for recurrence and mortality. As most of the organic changes caused by smoking are reversible within a period of 6 weeks, smoking cessation can have a significant impact on patients' prognosis. So, in order to assess the effect of smoking on the prognosis of pulmonary tuberculosis, medical records of 68 patients who were hospitalized at the HUJBB during the period from 2015 to 2020 were statistically analyzed to estimate the prevalence of smoking among patients; to compare clinical epidemiological variables, sex, age, length of stay and HIV coinfection in relation to smoking and to verify the association between smoking and the outcome (death and survival). Statistical tests of Chi-square adherence, Mann-Withiney test were applied, in addition to the elaboration of a prognostic risk indicator for PTB. Regarding the frequency of cases in the period from 2015 to 2020, there was an accumulated reduction of 80.07% in hospitalization for pulmonary TB. The age of the individuals ranged from 21 to 90 years, 33.82% were women and 66.18% were men. The proportion of men affected was almost twice as high as that of women, differing significantly by the chi-square test of adherence for equal expected proportions (χ2 = 6.485; df = 1; p-value = 0.0109). Regarding smoking, 50% of patients were smokers at some point in their lives. Regarding the clinical outcome, 11.76% died. A proportional difference (one-sided p = 0.00364) was observed for male smokers in relation to female smokers. The Pulmonary Tuberculosis Prognostic Risk Index showed statistically significant differences between sex and smoking. The results obtained in this study tend to support the hypotheses that being a man, a smoker, living with HIV AIDS and at an advanced age constitutes a risk for pulmonary tuberculosis, including death.